A reliable data flooding in underwater wireless sensor network - Ali, T. (Springer Verlag, 2014)
The problem of data gathering in the inhospitable underwater environment, besides long propagation delays and high error probability, continuous node movement also makes it difficult to manage the routing information during the process of data forwarding. Providing the better communication in UWSNs and maximize the communication performance in network is a significant issue due to volatile characteristics of water environment. This paper present our proposed a novel routing protocol called Layer by layer Angle Based Flooding (L2-ABF.), to handle the issue of horizontal communication between nodes on same depth level from the surface sinks, end-to-end delays and energy consumption. In L2-ABF, every node can calculate its flooding angle to forward data packet to the sinks, without using any explicit configuration and location information. The simulation results show that L2-ABF has some advantages over some existing flooding techniques and also can easily manage quick routing changes where node movements are frequent. Â© Springer Science+Business Media Singapore 2014.